Legal Review of Court Decision Number 26/Pdt.G/2024/Pn SBR: Case Study of Default in Contract Agreement - Evan Rahmandito; Mohamad Rafli Darmawan; Hilman Yahya Nafiansyah; Deni Yusup Permana; Diky Dikrurahman (Riviera Publishing, 2025)
This journal analyzes the legal aspects of default in a land title release agreement based on Court Decision Number 26/Pdt.G/2024/PN Sbr. The case involves the Plaintiff seeking compensation after Defendants PT Caruban Jaya Persada and two individuals failed to fulfill obligations in a land rights release agreement concerning parcels of land in Warugede Village, Depok Subdistrict, Cirebon Regency, valued at Rp3,311,182,000.00. The Defendants allegedly failed to make full payments and neglected other agreed terms, prompting the Plaintiff to file a claim under Article 1239 of the Indonesian Civil Code (KUH Perdata). This study employs a juridical analysis of legal documents, including the court decision and relevant legal provisions such as Article 1239 of the Indonesian Civil Code. Legal interpretation methods were used to assess the contractual dispute and its resolution. The court found the Defendants in default and ordered them to vacate the land and compensate the Plaintiff for financial losses incurred. The court's ruling emphasized the legal consequences of breaching contractual agreements, highlighting the enforceability of legally binding agreements under Indonesian civil law. The study concludes that Indonesian civil law provides robust protection for aggrieved parties in contractual disputes through Article 1239, ensuring that contract defaults lead to legally enforceable remedies. Adherence to contractual obligations is essential to avoid severe legal and financial consequences.